CXCL13 and Its Receptor CXCR5 in Cancer: Inflammation, Immune Response, and Beyond - Kazanietz, Marcelo G.; Durando, Michael; Cooke, Mariana (Frontiers in Endocrinology, 2019)
It is well established that the chemokine C-X-C motif ligand 13 (CXCL13) and its receptor, the G-protein coupled receptor (GPCR) CXCR5, play fundamental roles in inflammatory, infectious and immune responses. Originally identified as a B-cell chemoattractant, CXCL13 exerts important functions in lymphoid neogenesis, and has been widely implicated in the pathogenesis of a number of autoimmune diseases and inflammatory conditions, as well as in lymphoproliferative disorders. Current evidence also indicates that the CXCL13:CXCR5 axis orchestrates cell-cell interactions that regulate lymphocyte infiltration within the tumor microenvironment, thereby determining responsiveness to cytotoxic and immune-targeted therapies. In this review, we provide a comprehensive perspective of the involvement of CXCL13 and its receptor in cancer progression. Studies in recent years postulated novel roles for this chemokine in controlling the cancer cell phenotype, and suggest important functions in the growth and metastatic dissemination of solid tumors. Carcinogens have been found to induce CXCL13 production, and production of this chemokine within the tumor milieu has been shown to impact the proliferation, migration, and invasive properties of cancer cells.. Thus, the complex networks of cellular interactions involving tumoral CXCL13 and CXCR5 integrate to promote cancer cell autonomous and non-autonomous responses, highlighting the relevance of autocrine and paracrine interactions in dictating the cancer phenotype. Dissecting the molecular and signaling events regulated by CXCL13 and how this chemokine dynamically controls the interaction between the cancer cell and the tumor microenvironment is key to identify novel effectors and therapeutic targets for cancer treatment.